The Role of Human Resource Management in Improving Educational Quality in Primary Schools - Rifaldi H. Nasir; Andi Indriani Ibrahim; Rosida P. Adam; Wisra Matalatta; Lindanur Sipatu (Al-Qalam Institue, 2026)
This study aims to analyze the role of Human Resource Management (HRM) in improving educational quality in elementary schools. The research applies a qualitative case study approach to explore HRM practices, including teacher allocation, learning process management, leadership roles, and teacher performance evaluation. Data were collected through interviews, observation, and documentation involving principals and teachers, and analyzed using data condensation, data display, and verification techniques. The findings reveal that teacher allocation is relatively adequate, although continuous evaluation is still required. The learning process is implemented in a structured manner, yet still faces challenges in instructional variation and learning support. The principal plays an important role in providing direction and motivation through meetings, supervision, and mentoring, although consistency remains an issue. Teacher performance evaluation is conducted regularly, but follow-up actions need improvement. The study implies that effective HRM contributes significantly to educational quality improvement by strengthening teacher performance and school management systems. It also provides practical insights for improving leadership consistency, instructional quality, and evaluation effectiveness in schools, while highlighting the need for broader future studies across different educational contexts.